Pengaruh Electronic Word Of Mouth Terhadap Online Purchase Intention Melalui Brand Image Sebagai Variabel Mediasi - Adinda Indriana; Asep Muhamad Ramdan; R. Deni Muhammad Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research was aimed at determining the mediation’s influence of brand image in the relationship of electronic word of mouth on online purchase intention. The research method used in the research was descriptive and associative with quantitative. The populations in the research were college student in Sukabumi as a followers @scarlett_whitening instagram account, while using probability sampling method by distributing online questionnaires to 400 respondents. The technique of analyzing data applied by the researcher was Structural Equation Modelling (SEM) by using software IBM SPSS AMOS 24. The results of the research show that electronic word of mouth positively and significantly toward brand image, brand image influences positively and significantly toward online purchase intention, and brand image mediates the relationship between electronic word of mouth on online purchase intention. Keywords: Electronic Word of Mouth, Brand Image, Online Purchase Intention